(untitled) (Journal of Pharmaceutical Negative Results, 2021)
Background: Atopic dermatitis (AD) is a common inflammatory skin disorder causing erythematous lesions and abnormalities in microvascular structure. The cross-sectional study was done from January 5 to July 5, 2019, and it was carried out in Watim medical and dental college, Rawat to ascertain whether the mean age, standard deviation, and p-value were significant. Objectives: The purpose of this study is to examine the morphology of the blood vessels in the erythematous skin as well as the age of the patients with atopic dermatitis that may significantly differ from that of healthy individuals. Study design: A cross-sectional study. Place and duration of study. Department of pathology Watim medical and dental college, Rawat Pakistan From 05-Jan 2019 To 05-Jan 2020 Methods: The sample of this cross-sectional study was obtained from the department of pathology Watim medical and dental college, Rawat l starting in January 05- 2019 and up to 05- july 2019 As the total number, we have 100 patients who are diagnosed with atopic dermatitis (AD). The age of each patient was also uploaded. The morphology of veins in erythema eruptions was investigated with the use of dermoscopy. Unlike in my previous research, I used statistical analysis to discover the mean age and standard deviation. A p-value was calculated to assess the level of the discovered alterations in blood vessel morphology. Data analysis happened through statistical software and it meant that the accuracy and reliability would be in the findings of the research. Before the study could begin, the university ethicscommittee approved it. Results The study involved 100 patients with atopic dermatitis who attended Watim medical and dental college, Rawat aged between 18 and 65 years (mean age 35. 4, SD 12. 7) and is shown in (Table 1). The analysis of the blood vessel morphology in the erythematous skin of the patients revealed that two-thirds (60%) of them had altered morphology while one-third (40%) of the patients had normal morphology (Table 2). The statistical analysis identified a significant difference between the normal and the distorted vascular architecture with a p-value of 0. 045 (Table. 4). The study's ranking of the high incidence of vascular changes in atopic dermatitis lesions emphasizes the possible correlation between blood vessel transformations and the outcome of skin condition rashes (see Table 5). Conclusion The present study stresses important vasculature modifications in atopic dermatitis, and consequently, sheds light on their key role in the development of disease pathophysiology. Potential future targeted therapies on these vascular alterations might be more effective as compared to the therapy with just improvement in clinical results.